Determinant macroeconomic factors for consumers´ default in Brazil - Melo, Marcelo Miranda; Gomes, José Weligton Félix (Nexos Econômicos, 2019)
This research investigated major macroeconomic factors for consumers´ default in the Brazilian economy. The methodology applied was VAR analysis with Granger causality and impulse response function approaches. Moreover, found out what economic theory stream is applicable to the Brazilian economy with respect this issue. Results pointed out unemployment rate, credit availability and expectation rate the most sensitive macroeconomic variables to consumers´ default rate in Brazil. An employment rate shock of +23.14% will provoke a sharp increase of +66,66% in consumers´ default rate. On the other side, credit availability shock of +15.06% will contribute to -32,40% effect in consumers´ default rate. An optimistic shock of expectation rate of +14.50% will indicate -25,50% effect in consumers´ default rate. Monetary policy seems to affect consumers´ default rate through interest rates, however inflation seems to be an irrelevant factor to this ratio. Main results also suggest that credit, GDP and consumers´ expectation rate is fully linked to consumers´ default rate in the opposite direction. Interest rates and unemployment rate are also linked to consumers´ default rate in the same direction.